Effects of score-line on internal and external load in soccer small-sided games - Lorenzo-Martinez, M.; de Dios-Álvarez, V. M.; Padrón-Cabo, A.; Costa, P. B.; Rey, E. (International Journal of Performance Analysis in Sport, 2020)
The aim of this study was to analyse the effect of the score-line on the internal and external load in soccer small-sided games (SSGs). Thirty male semi-professional soccer players participated in an acute crossover design study. Players performed 4 series of 4 vs 4 with a game duration of 4 min. The data corresponding to players` external load were collected using a portable Global Positioning System device and players` internal load using rating of perceived exertion. The results showed that players covered significantly higher total distance (effect size [ES]: 0.63-55), medium-intensity distance (ES: 0.81-82), and high-intensity running distance (ES: 0.86-0.53) when the final result of SSGs was a draw in comparison when losing or winning. Players` power score was significantly higher when the final result of SSGs was a draw compared to when was a loss (ES: 0.77). On the contrary, players covered significantly shorter walking distance when drawing compared to losing (ES: 0.55) and winning (ES: 0.63). Present results indicate players` external load during SSGs is related to the final score-line. In order to maximise players` external load during SSGs, teams should be as balance as possible to increase the probability of a draw score-line.